2013
DOI: 10.3390/ijms140817029
|View full text |Cite
|
Sign up to set email alerts
|

UVB-Stimulated TNFα Release from Human Melanocyte and Melanoma Cells Is Mediated by p38 MAPK

Abstract: Ultraviolet (UV) radiation activates cell signaling pathways in melanocytes. As a result of altered signaling pathways and UV-induced cellular damage, melanocytes can undergo oncogenesis and develop into melanomas. In this study, we investigated the effect of UV-radiation on p38 MAPK (mitogen-activated protein kinase), JNK and NFκB pathways to determine which plays a major role in stimulating TNFα secretion in human HEM (melanocytes) and MM96L (melanoma) cells. MM96L cells exhibited 3.5-fold higher p38 activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…[28][29][30][31] Therefore, in addition to the B-Raf/ERK pathway, the activation of NF-jB or inactivation of AP-1 may play a role in melanoma development. 21,25 Our study identified significantly increased levels of phosphorylated ERK and JNK after exposure to both UVA and UVB. The phosphorylation persisted for a longer time with UVA.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…[28][29][30][31] Therefore, in addition to the B-Raf/ERK pathway, the activation of NF-jB or inactivation of AP-1 may play a role in melanoma development. 21,25 Our study identified significantly increased levels of phosphorylated ERK and JNK after exposure to both UVA and UVB. The phosphorylation persisted for a longer time with UVA.…”
Section: Discussionmentioning
confidence: 69%
“…Furthermore, only a few investigations have compared the effects of different wavelengths. In melanocytes and melanoma, UV has been shown to induce phosphorylation of the p38 and JNK/stress‐activated protein kinase pathways, whereas NF‐κB remains at constantly high expression . The B‐Raf/ERK pathway has been suggested as the central pathway involved in melanoma development and progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…López et al, reported that paracrine protective effects of CM from UVB-irradiated KC on MC involved regulation of various signaling pathways including proinflammatory and p53-dependent apoptotic pathways [42]. Our study demonstrated that the microenvironment created by KC reversed damaging effects of UVB on MC by reducing activation of caspase-3 and p53 that play a crucial role in UVR-mediated apoptosis associated with DNA damage [25,26], and by downregulating inflammatory markers including NF-κB activation and TNF-α levels implicated in photodamaged skin [46,47]. Nevertheless, depletion of Nrf2 in KC resulted in suppression of its protective effects on UVB-mediated DNA damage, apoptosis and inflammatory response in MC.…”
Section: Discussionmentioning
confidence: 93%
“…The algal extract introduced at a final content of 5% (w/w) allowed significant anti UV-B activity. UV radiation induces diverse effects for human skin like sunburn, inflammation, alteration of cytokine levels in cells found in the epidermis and dermis, and causes skin aging by the reaction of free radicals and reactive oxygen species and/or formation of aggressive malignant skin cancer (Muthusamy and Piva 2013). The UV-B-induced pyrimidine dimers in DNA can lead to a form of programmed apoptosis or can cause DNA replication errors.…”
Section: Detection Of Palythenic Acidmentioning
confidence: 99%